Volume 4A: Dynamics, Vibration, and Control 2014
DOI: 10.1115/imece2014-38441
|View full text |Cite
|
Sign up to set email alerts
|

Two-Way Fluid-Structure Coupling in Vibration and Damping Analysis of an Oscillating Hydrofoil

Abstract: Fluid-structure interaction (FSI) and unavoidable vibrations are important characteristics in the operation of hydropower structures and must be taken into account in the analysis and design of such equipment. Hydrodynamic damping influences the amplitude of vibrations and is directly related to fatigue problems in hydraulic machines which are of great importance. The aim of this study is to investigate the coupled effects of flowing fluid on a simplified hydrofoil by using three-dimensional two-way fluid-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 18 publications
0
8
0
3
Order By: Relevance
“…The second case is an FSI problem with the global uniformity mesh type and using the classical case of an elastic plate vibration. 24 The initial undeformed mesh is shown in Figure 4; the flow field has 2.48 Â 10 4 nodes and 4.91 Â 10 4 triangular elements and the elastic plate structure is modeled with 28 red labels. Prior to the vibration, the unstressed elastic plate is end-fixed with a nondimensional height of 1.0, a width of 0.4, a density of 2550 kg/m 3 , Young's modulus of 2.5 MPa, a Poisson's ratio of 0.35, and a kinetic viscosity of 0.2.…”
Section: Fsi Problemmentioning
confidence: 99%
“…The second case is an FSI problem with the global uniformity mesh type and using the classical case of an elastic plate vibration. 24 The initial undeformed mesh is shown in Figure 4; the flow field has 2.48 Â 10 4 nodes and 4.91 Â 10 4 triangular elements and the elastic plate structure is modeled with 28 red labels. Prior to the vibration, the unstressed elastic plate is end-fixed with a nondimensional height of 1.0, a width of 0.4, a density of 2550 kg/m 3 , Young's modulus of 2.5 MPa, a Poisson's ratio of 0.35, and a kinetic viscosity of 0.2.…”
Section: Fsi Problemmentioning
confidence: 99%
“…The NWT simulations are made with different assumptions in CFD programs. Waves with certain qualities can be created using simulations [6]. In a study by Liu et al, a numerical simulation with Reynolds-Averaged-Navier-Stokes (RANS) equation is done for two-dimensional NWT modeling utilizing the Volume of Fluid (VOF) approach [7].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that this approach is suitable for the prediction of the vibration amplitude with a maximum deviation of around 8.82% for the hydrodynamic damping. Liaghat et al [25] also studied the dynamic response of the first bending mode of a hydrofoil by using two-way FSI simulations. They numerically found the linear relationship between the hydrodynamic damping and the free-stream velocity.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, most of the literature related to the study of hydrofoils under vortex shedding flows deals with: (i) the prediction of the vortex shedding frequency for free-wake cavitation conditions [12,15,16,[29][30][31][32], (ii) the influence of the wake cavitation on the vortex shedding dynamic behavior [4,[20][21][22][23], and (iii) the prediction of the vibration amplitudes of hydrofoil under lock-off and lock-in conditions when no wake cavitation occurs [17,[24][25][26][27][28]. However, solely Ausoni et al [6] experimentally studied the interaction between wake cavitation and the dynamic response of a hydrofoil under a lock-in condition.…”
Section: Introductionmentioning
confidence: 99%